INTRODUCING STUDENTS TO TODAY'S BIODIVERSITY AND ECOLOGICAL PROBLEMS (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article discusses the importance of starting school-age children with knowledge related to ecology, especially the ecosystem. Also, to convey and explain to the young generation about the big changes in ecology in recent years, to explain in detail about the need to convey the benefits of nature to the generations without disturbing the balance, and to the thoughts about further increasing their love for nature. has been discussed.
Keywords: Local (local), Regional (regional), Global (universal), megapolis, microclimate.